“Learning from the past, to improve the future”: content analysis of the transition of the higher education system in Indonesia - Kudus, Imanudin; Nurasa, Heru; Widianingsih, Ida; Karlina, Nina; Jawan, Jayum Anak (Taylor and Francis, 2025)
The university admission selection system in Indonesia has gone through significant transformations from the colonial era to the present. This research analyses the transformation of Indonesia’s university admission selection system from the colonial era to the present. It uses a narrative approach and organisational change theory to identify the dynamics, challenges and opportunities in each phase of development. Starting from social discrimination during the colonial era, the shift to a military-based education system during the Japanese occupation, to decentralisation and digitalisation in the reform era and the present. The research findings show that the transformation of the selection system reflects not only technical changes, but also changes in social, political and economic values in the context of higher education. Nowadays, technologies such as the Computer-Based Written Test (Ujian Tertulis Berbasis Komputer/UTBK) accelerate the transparency and efficiency of selection. However, challenges such as disparities in access, quality of human resources, and relevance of the curriculum to the labour market remain key issues. This research suggests evidence-based strategies to improve the higher education selection system, including technology enhancement, access equity, and collaboration between universities, industry, and government to build an inclusive, competitive, and globally relevant higher education system.